Transcriptomic response of male Anastrepha fraterculus (Diptera: Tephritidae) to sexual stimulation by host plant volatiles - Belliard, Silvina Ahnahi; Hurtado, Juan; Matzkin, Luciano M.; Revale, Santiago; Segura, Diego Fernando (Elsevier, 2025)
Anastrepha fraterculus is a major pest of fruits in South America. Previous studies revealed that males exposed to volatiles from guava, a likely ancestral host, intensify courtship behavior and increase mating success. However, the molecular and physiological mechanisms underlying this effect remain unknown. Here, we explore the impact of exposure to guava essential oil volatiles on the gene expression profile of adult male heads through de novo transcriptome assembly and differential expression analysis. We found 678 differentially expressed genes (FDR < 0.05 and |FC| > 2), 308 of which were over-expressed in exposed males and 370 in non-exposed males. The exposure treatment affected the transcription of genes putatively involved in mucus-forming, lipid metabolism and neuropeptide processing. Our findings provide the first insights into the molecular mechanisms underlying sexual stimulation in A. fraterculus males triggered by host fruit volatiles.